Pengaruh Tingkat Harga terhadap Volume Penjualan Kain Songket: Studi Empiris di Desa Borik, Kecamatan Satar Mese Barat, Kabupaten Manggarai - Novelianus Aristo Jemarut; Sulfaidah Sulfaidah; Sitti Marlina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Songket cloth is one of the traditional handicraft products that holds both economic value and cultural significance for the community of Borik Village, Satar Mese Barat District, Manggarai Regency. This woven product is not only used as a complement to traditional attire but also serves as a primary source of livelihood for most of the local population. In an increasingly competitive market environment, price fluctuations are often assumed to influence the sales volume of such handicraft products. Based on this context, this study aims to analyze the extent to which price levels affect the sales volume of songket cloth in Borik Village. The research employed a quantitative approach with an associative type of study. Data were collected through observation, interviews, and documentation involving songket weavers and traders. Data analysis was conducted using a simple linear regression to examine the relationship between the price level variable (X) and the sales volume variable (Y). The results indicate that the price level has no significant effect on sales volume, as reflected by a significance value of 0.665 (> 0.05). The coefficient of determination (R²) of 0.007 shows that the price level only explains 0.7% of the variation in sales volume, while the remaining 99.3% is influenced by other factors not examined in this study. Therefore, it can be concluded that price is not the main factor influencing the sales volume of songket cloth in Borik Village; instead, it is likely affected by other aspects such as product quality, motif uniqueness, and consumer preference toward the cultural values embedded in songket cloth.